Characterising agrometeorological climate risks and uncertainties: Crop production in Uganda - Drake Mubiru; Everline Komutunga; Ambrose Agona; Anne Apok; Todd Ngara (South African Journal of Science)
Uganda is vulnerable to climate change as most of its agriculture is rain-fed; agriculture is also the backbone of the economy, and the livelihoods of many people depend upon it. Variability in rainfall may be reflected in the productivity of agricultural systems and pronounced variability may result in adverse impacts on productivity. It is therefore imperative to generate agronomically relevant seasonal rainfall and temperature characteristics to guide decision-making. In this study, historical data sets of daily rainfall and temperature were analysed to generate seasonal characteristics based on monthly and annual timescales. The results show that variability in rainfall onset dates across Uganda is greater than the variability in withdrawal dates. Consequently, even when rains start late, withdrawal is timely, thus making the growing season shorter. During the March-May rainy season, the number of rainy days during this critical period of crop growth is decreasing, which possibly means that crops grown in this season are prone to climatic risks and therefore in need of appropriate adaptation measures. A time-series analysis of the maximum daily temperature clearly revealed an increase in temperature, with the lower limits of the ranges of daily maximums increasing faster than the upper limits. Finally, this study has generated information on seasonal rainfall characteristics that will be vital in exploiting the possibilities offered by climatic variability and also offers opportunities for adapting to seasonal distribution so as to improve and stabilise crop yields.